Treatment adherence of antiretroviral therapy among people living with HIV/AIDS - Sharma, B; Joshi, K (Journal of Chitwan Medical College, 2017)
Adherence to Antiretroviral therapy (ART)is a principle predictor for the success of Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome treatment. Highly Active Antiretroviral Therapy (HAART) has led to the reduction of mortality and the improvement of the quality of people living with HIV/AIDS. It has been estimated that at least 95% adherence with therapy is required to reduce HIV viral load. Non-adherence to treatment can lead to inadequate suppression of viral replication, continued destruction of CD4 cells, progressive decline in immune function and disease progression. The aim of the study is to assess treatment adherence of antiretroviral therapy among people living with HIV/AIDS at Seti Zonal Hospital, Kailali. A descriptive cross-sectional study was conducted among 160 people living with HIV/AIDS in ART Clinic, Seti Zonal Hospital, Kailali. Non-probability purposive sampling technique was used for data collection between 22/03/2071 to 02/04/2071. Informed consent was obtained prior collecting data from self-structured questionnaire using interview technique. Collected data were entered and analyzed by SPSS 17.0 and represented by using percentage, frequency, mean, standard deviation and chi- square test. Results: Among the respondents majority of them were “female” 85(53.1%) sex, from age group “31-45 years” 85 (53.1%), ethnicity “minority group/ Dalit” 76 (47.5%) and education “illiterate” 79 (50.3%). The mean adherence rate for one month was found to be 89.92%. Majority of the respondents were adherent to ART 96 (60%). Regarding non-adherence the major barrier was “forgetting” 52 (45.6%). There is statistically significant association between age of the respondents (p=0.04), ethnicity (p=0.03) and prescribed ARV regimen (p=0.02) with drug adherence. More than half of the respondents were adherent to ART. Among non-adherent, the most of them reported “forgetting to take drug”. Non adherence patient and family members can be addressed with proper counseling and motivation for their drug compliance.